3D‐Printed PDMS/Graphene Sensors with Tunable Sensitivity via Temperature‐Induced Crosslinking for Pressure Applications - Chong‐You Chen; Sepidar Sayyar; Johnson Chung; Guan‐Yu Chen; Gordon G. Wallace (Advanced Electronic Materials)
Abstract The development of polydimethylsiloxane (PDMS) graphene composites with high graphene content, employed to formulate printing ink for the fabrication of tunable multilayer pressure sensors via 3D printing is presented. This study demonstrates an efficient preparation technique capable of incorporating a high loading of edge‐functionalized expanded graphene into PDMS while minimally affecting the inherent crosslinking properties of the matrix. Graphene addition enhances electrical conductivity and rheological investigations reveal improves the printability of PDMS. Three sensor configurations differing in layer order and conductivity through piezoresistive characterization, demonstrating their excellent sensitivity and tunability with a gauge factor of ≈20 are evaluated. This performance is comparable to, and in some cases exceeds, similar structures reported in the literature. The assessment of the real‐world application potential of the PDMS/graphene pressure sensor in monitoring human movements during typical everyday situations reveals promising results. These findings suggest that the sensors developed here hold significant promise for diverse pressure‐sensing applications across various fields, including wearables, medical diagnostics, and industrial automation .